Pengaruh persepsi manfaat, kemudahan penggunaan, risiko terhadap minat menggunakan dompet elektronik - Muhammad Farid Iffat; Ayu Chairina Laksmi (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2023)
This study aims to analyse and determine the variables perceived benefits, perceived ease of use, perceived risk can influence people's interest in using electronic wallet services. This research was conducted using a quantitative method using a questionnaire distributed online. The number of respondents in this study was 265 in the people of Medan City. This study uses data analysis with Structural Equation Modelling analysis with the Partial Least Square (PLS) method assisted by SmartPLS 3.0 software. The results of this study indicate that perceived benefits, perceived ease of use, and perceived risks have a positive and significant impact on the intention to use electronic wallets.